Femtosecond fiber laser-induced surface structuring of metals at cryogenic temperatures - G.S. Boltaev; A.Abu Baker; A.S. Alnaser (Applied Surface Science Advances, 2023)
Creating nano/micron-sized topographies on metal surfaces holds great promise across many optical, biomedical, and industrial applications. Among the most effective and widespread techniques for producing precisely organized features on material surfaces is laser-induced periodic surface structuring (LIPSS). Herein, we utilize a femtosecond fiber laser to generate LIPSS on low- and high-thermal-conductivity materials under extremely low temperature conditions, and we compare the results with those achieved at room temperature. To the best of our knowledge, this is the first instance of conducting laser-induced surface structuring experiments under cryogenic conditions. We examine how the initial thermal conditions of the substrate affect the patterns that form on its surface. Different surface characteristics emerge based on the substrate's thermal properties and the intensity of the laser beam. For instance, when we subject a silver substrate (known for high thermal conductivity) and tungsten substrate (known for high melting point) to laser-induced surface structuring at a low temperature of 110 K, they develop high-spatial frequency ripples on the surface oriented parallel to the polarization direction of the laser with a periodicity of around 100 nm, which is one-tenth the wavelength of the irradiating laser (1030 nm). In contrast, the cooled stainless-steel substrates (known for low thermal conductivity) exhibit no alterations in the patterns or their periodicity compared to substrates structured at room temperature. Furthermore, the formation of well-defined LIPSS patterns continue to persist on the surface of the cooled copper substrate, even when using large number of laser pulses. However, there exist specific localized regions of increased energy that disrupt the uniformity of the LIPSS pattern formation when the process is carried out at room temperature.